RECENT ADVANCES IN HYDROGELS FOR BIOMEDICAL APPLICATIONS - Das, Surojeet; Kumar, Vivek; Tiwari, Rini; Singh, Leena; Singh, Sachidanand (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Hydrogels are three-dimensional polymeric network, capable of entrapping substantial amounts of fluids. Hydrogels are formed due to physical or chemical cross-linking in different synthetic and natural polymers. Recently, hydrogels have been receiving much attention for biomedical applications due to their innate structure and compositional similarities to the extracellular matrix. Hydrogels fabricated from naturally derived materials provide an advantage for biomedical applications due to their innate cellular interactions and cellular-mediated biodegradation. Synthetic materials have the advantage of greater tunability when it comes to the properties of hydrogels. There has been considerable progress in recent years in addressing the clinical and pharmacological limitations of hydrogels for biomedical applications. The primary objective of this article is to review the classification of hydrogels based on their physical and chemical characteristics. It also reviews the technologies adopted for hydrogel fabrication and the different applications of hydrogels in the modern era.